Analysis of Digital Marketing Strategies in Increasing Sales of Fashion Products (Sendal, Flat Shoes, and Heels) Koaki Medan in an Islamic Economic Perspective - Miranda, Miranda; Nawawi, Zuhrinal M. (Universitas Ibn Khaldun, 2024)
This research aims to increase sales of fashion products such as sandals, flat shoes, and heels from the Koaki Medan brand from an Islamic perspective. The results of this research show that fashion sandals, flat shoes, and heels products from the Koaki Medan brand carry out a digital marketing strategy using two methods, namely by utilizing social media and using e-commerce such as Shopee from an Islamic economic perspective. By using this strategy, it is easy for businesses or entrepreneurs to introduce their products to their target market. The method used in this research is a qualitative method by observing through social media a local brand from Medan, namely the brand name Koaki. This research also uses previous research related to the required research problem. This method helps researchers answer the problem topic being researched.